2008
DOI: 10.1007/s12272-001-1203-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fucoidan extracts on CCl4-induced liver injury

Abstract: The aim of this study was to elucidate the antioxidant properties of fucoidan extracts (FE) against CCl(4)-induced oxidative stress by monitoring the levels of glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx). Female, Sparague-Dowley rats were administered with FE (100 mg/kg daily) for 14 days and CCl(4) on the 15'th day, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…In the same aspect, Park et al concluded that fucoidan applies anti-inflammatory effects by inhibiting the expression of pro-inflammatory cytokines in vitro and in vivo, together with a restricted antibacterial effect in vivo. Furthermore, fucoidan enhanced the production of pro-inflammatory cytokines, IL-6, IL-8 and TNF-α in human neutrophil and delay neutrophil apoptosis [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In the same aspect, Park et al concluded that fucoidan applies anti-inflammatory effects by inhibiting the expression of pro-inflammatory cytokines in vitro and in vivo, together with a restricted antibacterial effect in vivo. Furthermore, fucoidan enhanced the production of pro-inflammatory cytokines, IL-6, IL-8 and TNF-α in human neutrophil and delay neutrophil apoptosis [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…31) Indeed, it has been reported that fucoidan showed significant antioxidative activity in immune cells, neurons, and the liver. 10,32) Kang et al (2008) have reported that fucoidan showed antioxidative properties by increasing such antioxidative enzymes as SOD and GPx against CCl 4 -induced acute liver injury. 19) In agreement, we observed that fucoidan increased SOD and GPx with concomitant reduction of MDA production in a liver homogenate and the plasma of rats with DMN-induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…10,32) Kang et al (2008) have reported that fucoidan showed antioxidative properties by increasing such antioxidative enzymes as SOD and GPx against CCl 4 -induced acute liver injury. 19) In agreement, we observed that fucoidan increased SOD and GPx with concomitant reduction of MDA production in a liver homogenate and the plasma of rats with DMN-induced liver fibrosis. We investigated whether the anti-oxidative effect of fucoidan on chronic liver fibrosis was mediated by Nrf2 which plays a critical role in maintaining the cellular redox balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyeok intake did not show any significant associations with the risk of breast cancer in the present study, a finding which may be due to the low consumption frequency and low variation in miyeok intake among the subjects. However, U. pinnatifida (miyeok) has been reported to suppress mammary tumour growth in rats (25) , while fucoidan and fucoxanthin from U. pinnatifida has antitumour (39,40) and antioxidant activities (41) . Therefore, further studies are needed to investigate the relationship between miyeok intake and breast cancer risk in other research settings including areas with a large variation of miyeok intake.…”
Section: Discussionmentioning
confidence: 99%